1, 4‐Michael Addition – The Analytical Way for Quantitative Sensing of Neurotransmitter at Bare Gold Electrode in Physiological Solution in the Presence of Interfering Biogenic Compounds. Issue 9 (27th August 2013) - Łuczak, Teresa
Abstract Electrooxidation of norepinephrine in the presence a nucleophile was investigated on a bare gold electrode. Electrochemically produced norepinephrinequinone undergoes an attack by morpholine as nucleophile via 1, 4‐Michael addition. The reaction products were identified by electrospray ionization mass spectrometry. The procedure used was suitable for quantitative norepinephrine determination in the concentration range from 1×10−9 M to 8×10−4 M with a detection limit of 8.7×10−10 M in a samples containing an excess of ascorbic and uric acids. The proposed method is simple, green which means that it does not require the use of toxic compounds and solvents and thus is promising for detection of norepinephrine in physiological environment.